2013
DOI: 10.7314/apjcp.2013.14.9.5441
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Pelvic Drainage as a Predictive Factor For Anastomotic Leakage after Surgery for Patients with Rectal Cancer

Abstract: considerable extra cost, increased in-hospital morbidity and mortality, impaired pelvic organ function (Eriksen et al., 2005; Law et al., 2007; Lee et al., 2008;Riss et al., 2011). Although there are multiple risk factors, such as being male, advanced age, severe obesity, lower tumor site (less than 4cm from the anal verge) and the reduction of TSGF in POD5, which are associated with anastomotic leakage have been reported in our previous study (Yang in individual patients on account of the absence of a early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 59 publications
0
16
2
Order By: Relevance
“…In a study by Yang et al, 2013 they reported an AL of 7.6%, inspite that this rate seems lower than in this study, however they included the whole rectum (including upper rectum), they excluded hand-sewn anastomoses and an acquired infection in the postoperative period other than leakage. Yang et al (2014) demonstrated an anastomotic leakage in anterior resection with a double stapling technique of 7.6% between the 6 th and 12 th postoperative days compared to 12% in the stapled group of this study, and this difference may be due the small sample size (n=25) in this study compared to (n=753), while leakage in this study was diagnosed between the 6 th and 8 th postoperative days.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a study by Yang et al, 2013 they reported an AL of 7.6%, inspite that this rate seems lower than in this study, however they included the whole rectum (including upper rectum), they excluded hand-sewn anastomoses and an acquired infection in the postoperative period other than leakage. Yang et al (2014) demonstrated an anastomotic leakage in anterior resection with a double stapling technique of 7.6% between the 6 th and 12 th postoperative days compared to 12% in the stapled group of this study, and this difference may be due the small sample size (n=25) in this study compared to (n=753), while leakage in this study was diagnosed between the 6 th and 8 th postoperative days.…”
Section: Discussioncontrasting
confidence: 55%
“…Dusky, cyanosed, bowel ends indicate an inadequate arterial supply and the affected Segment important for anastomosis and stoma formation involving the large bowel (Joyce et al, 2002;Goulder et al, 2012). In this study, all the preceding factors for anastomotic integrity were considered and applied by the surgeon intra-operatively, and since irradiated bowel or previous chemotherapy are contributing factors in anastomotic failure and leakage (Trencheva et al, 2013;Yang et al, 2013), all patients in this study didn't receive neoadjuvant chemoradiation regarding the early stage (T2) and relatively the high distance from the anal verge 9.6±2.0 cm in group I and 9.9±2.4 cm in group II.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies 16,24,30,31,35,49 evaluated peritoneal and systemic biomarkers of ischaemia in the context of AL following colorectal surgery. Matthiessen and colleagues 31 reported a statistically significant increase in the lactate/pyruvate (L/P) ratio on POD 5 and 6 in four patients with AL diagnosed up to POD 14 (median POD 6), and another three with AL diagnosed after discharge (median POD 20, range [18][19][20][21][22].…”
Section: Biomarkers Of Ischaemiamentioning
confidence: 99%
“…a daily rise of around 50 units being most predictive Burke, 2017, [17] CRP (POD5, cutoff value:132 mg/l), CRP (sensitivity 70%, specilficity 76.6%), Ismail, 2017, [18] Serum CRP and PCT (POD3), Drain TNF-a and bacterial proliferation (POD5) Komen, 2014, [19] LBP An increase in the average initial value at the first postoperative day with 1 standard deviation increased the risk of leakage by 1.6 times. Urszula, 2016, [21] PCT (POD1, cutoff value:1.09 ng/mL) Sensitivity 87%, specilficity 87% Tarik, 2016, [22] Peritoneal IL-6 (POD1, cutoff value:3091 pg/ml); peritoneal IL-10 (POD1, cutoff value:504 pg/ml) Peritoneal IL-6 (sensitivity 86%, specilficity 52%), peritoneal IL-10 (sensitivity 86%, specilficity 62%) Elyamani, 2011, [23] Cytokines (IL-6, IL-10, TNF), microbiological study (Escherichia coli, Klebsiella, Pseudomonas species, and bacteriod microorganism) Käser, 2014, [25] Hyponatremia Sensitivity 23%, specilficity 93% Liu, 2013, [26] PH: POD3, cutoff value: 6.978 Sensitivity 98.7%, specilficity 94.7% Liron, 2016, [27] CEA (1000 ng/mL) drainage fluid after rectal surgery with anastomosis, is a marker of AL. A cut-off value of 6.978 determined at 25°C on POD3 maximizes the sensitivity and specificity [26].…”
Section: Some Uncommon Markers In Drainagementioning
confidence: 99%
“…Urszula, 2016, [21] PCT (POD1, cutoff value:1.09 ng/mL) Sensitivity 87%, specilficity 87% Tarik, 2016, [22] Peritoneal IL-6 (POD1, cutoff value:3091 pg/ml); peritoneal IL-10 (POD1, cutoff value:504 pg/ml) Peritoneal IL-6 (sensitivity 86%, specilficity 52%), peritoneal IL-10 (sensitivity 86%, specilficity 62%) Elyamani, 2011, [23] Cytokines (IL-6, IL-10, TNF), microbiological study (Escherichia coli, Klebsiella, Pseudomonas species, and bacteriod microorganism) Käser, 2014, [25] Hyponatremia Sensitivity 23%, specilficity 93% Liu, 2013, [26] PH: POD3, cutoff value: 6.978 Sensitivity 98.7%, specilficity 94.7% Liron, 2016, [27] CEA (1000 ng/mL) drainage fluid after rectal surgery with anastomosis, is a marker of AL. A cut-off value of 6.978 determined at 25°C on POD3 maximizes the sensitivity and specificity [26]. Evidences showed that carcinoembryonic antigen (CEA) elevation were associated with the inflammation process that accompanies AL [19].…”
Section: Some Uncommon Markers In Drainagementioning
confidence: 99%